Lumpy price adjustments: a microeconometric analysis - Emmanuel Dhyne; Catherine Fuss; Hashem Pesaran; Patrick Sevestre (National Bank of Belgium, 2006)
This paper presents a simple model of state-dependent pricing that allows identifying the relative importance of both nominal and real factors in price rigidity. Using two rich datasets consisting of a large fraction of the price quotes used to compute the Belgian and French Consumer Price Indices, we are able to evaluate, the importance of the menu costs and to discriminate between idiosyncratic and common shocks that affect the marginal cost and/or the desired mark-up at the outlet level. We find that infrequent price changes are not necessarily associated with large menu costs. Indeed, real rigidities appear to play a significant role. We also find that asymmetry in the price adjustment may result from a trend in marginal costs and/or desired mark-ups rather than from asymmetric menu costs
Keywords: C51; C81; D21; 330; Sticky prices; menu costs; nominal and real rigidities; micro panels; Preisrigidität; Preis; Anpassung; Verbraucherpreisindex; Schätzung; Belgien; Frankreich